Perbandingan Tingkat Kejadian Amenorrhea Antara Penggunaan KB Suntik Depo Provera dan Cyclofem di Puskesmas Kalasan urwomartani Sleman Yogyakarta - Supriyadi, Agung, AgungDr. Anika Candrasari, M.Kes (2017)
Background: Use of contraception injections have been increase lately, especially in developing country, like Indonesia. The type of injectable contraception that often been used is cyclofem and Depo Provera, where Cyclofem is an injected contraceptive containing estrogen and progesterone and is used every month. While the Depo-Provera is an injected contraceptive those contain of progesterone only and can be used for three months. But a contraception injection has side effects, such as the incidence of amenorrhea that is the condition when the woman did not experience menstruation for 3 consecutive months. Purpose: To find out the level of comparison the incidence of amenorrhea between Depo Provera and Cyclofem in Clinics Kalasan Yogyakarta 2016 Method: The research methods that used in this research are cross-sectional and retrospective approach. Results: The results showed that the majority of users Cyclofem is aged 26-30 years (25.7%) with a high school education is the dominant (74.3%), the most work are housewives (60%), with the intensity of exercise is predominantly once a week (42.9%), BMI respondents is obese (25.7%) and duration of use is for 2-5 years (91.4%). While users of Depo-Provera the majority of users are 36-40 years as much as 25.7%, with a high school education (65.7%), the work is dominated by housewives (54.3%), exercise intensity is never exercise (57.1%), IMT most are obese (20%) and the duration of use for 2-5 years (77.1%). Based on the statistics calculation in the results show that the value of P = 0.000 (P < 0.05) which is means that there is a difference in use of type contraceptive injection (depo provera and cyclofem) against the incidence of amenorrhea on respondents. Research results also showed that the value of RP (prevalence ratio) of 0.241 with 95% confidence interval (0,015-0,173) which means that the use of contraceptive injection (depo provera and cyclofem) can be a protective factor for occurrence of amenorrhea. Conclusion: There is a difference between the use of depo-provera and cyclofem on incidence rate amenorrhea in Clinics Kalasan Yogyakarta 2016